АВСТРІАЦИЗМИ У МОВІ СУЧАСНОЇ АВСТРІЙСЬКОЇ ПРЕСИ - Карпік М.; Павличко О. (International Journal of Innovative Technologies in Social Science, 2019)
The proposed study is aimed at confirming the hypothesis that there exist two opposing trends in media discourse. On the one hand, there is a tendency to globalization; on the other hand, linguocultural communities are quite determined to preserve their culture and identity. To prove this hypothesis we analyzed a corpus of newspaper texts published over several years. Namely, we studied 1483 Austriacisms recorded by the dictionary Variantenwörterbuch des Deutschen. The objective was to discover the frequency in the use of certain Austriacisms and their Teutonic equivalents in Austrian newspaper Die Presse to identify convergent or divergent processes in the development trends of the German language in Austrian media discourse. The research showed that only 453 lexical units dominated in newspaper articles; it made 30% of 1483 codified Austriacisms. We found that 71 lexemes showed tendency to the parallel use in forms of Austriacisms and Teutonisms which makes less than 5 % of the total number of the lexical units. Such terms have predominantly similar pronunciation hence we can draw a conclusion that such phonemic similarity facilitates equal use of these Austriacisms and Teutonisms in newspapers and stipulates their convergence. These lexical units are not marked by any particular ethnocultural specificity. Furthermore, the analysis shows that the word stock denoting Austrian culture, traditions, and realia of daily life.